Utilizing on-board GPS in city buses to determine traffic conditions - Ikhwan Hafiz, Muhamad; Ng, Siew Ling (UTeM, 2018)
The traffic congestion has become a major concern to the society. It causes difficulties in journey planning while avoiding the traffic congestion. Increasing number of vehicles lead to traffic congestion, especially during peak hours. There are many Mobile Applications (App) which can update traffic conditions in certain routes, but these applications such as Waze requires the road users to manually update the traffic conditions. Besides that, the road users also require to be online to get the real-time traffic conditions. On the other hand, the traffic data of this App also will not be accurate if fewer people are using this app on that route. Therefore, this project aims to provide automatic updates on traffic conditions to each road user without the need of installing additional App and updates from the user. The traffic conditions are predicted using the onboard GPS data in the city buses. The traffic monitoring algorithm is developed using the Fuzzy Logic Algorithm. The result is displayed in a Graphical User Interface (GUI) and a push notification to the user’s smartphone. The accuracy of this system is 90.34% where the inaccurate data occurred mostly in the data at Pekan, Pahang area due to the unexpected road conditions such as the deflection of the road, uneven road, holes and wild animals crossing which cause the bus driver to slow down the speed.